Synthesis of Multi-Color Long Laser Pulses for Strong Attosecond Pulse Generation. (14th January 2015) - Li, Fei; Wang, Guo-Li; Zhao, Song-Feng; Zhou, Xiao-Xin
Abstract: We theoretically investigate the high-order harmonics and attosecond pulses generated in a single mid-infrared and synthesized two- and three-color fields. We demonstrate that one can obtain a sub-cycle field by combining two or more long pulses at incommensurate frequencies, if the phases and amplitudes of each field are properly optimized. Compared with the one-color field, the harmonic yields in synthesized fields can be enhanced more than two orders with the same total laser power. The technique of waveform synthesizing shows the possibility of generating intense single attosecond pulses by using longer driving laser pulses without the need of gating techniques with experiment.